2020
DOI: 10.1017/s003329171900388x
|View full text |Cite|
|
Sign up to set email alerts
|

Long-term cardiac outcomes of depression screening, diagnosis and treatment in patients with acute coronary syndrome: the DEPACS study

Abstract: Background To investigate the impacts of depression screening, diagnosis and treatment on major adverse cardiac events (MACEs) in acute coronary syndrome (ACS). Methods Prospective cohort study including a nested 24-week randomised clinical trial for treating depression was performed with 5–12 years after the index ACS. A total of 1152 patients recently hospitalised with ACS were recruited from 2006 to 2012, and were divided by depression screening and diagnosis at baseline and 24-week t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 37 publications
0
20
0
5
Order By: Relevance
“…of CHD patients with elevated depressive symptoms are at an increased risk of an acute cardiac event. 2,9 Relief of depressive symptoms could be a potentially modifiable factor for the reduction of acute cardiac events.…”
mentioning
confidence: 99%
“…Due to the importance of physical stress symptoms among CAD patients, several guidelines and scientific statements recommend screening CAD patients for psychological stress, including anxiety or depression [11]. The previous studies reported favorable effects of screening for depression in patients with recent acute coronary syndrome and subsequent management of psychosocial stress could improve long-term cardiac outcomes, stressing the importance of early detection of anxiety, or depression in CAD patients [12].…”
Section: Discussionmentioning
confidence: 99%